No protection of heart, kidneys and brain by remote ischemic preconditioning before transfemoral transcatheter aortic valve implantation: Interim-analysis of a randomized single-blinded, placebo-controlled, single-center trial. (15th March 2017) - Kahlert, Philipp; Hildebrandt, Heike Annelie; Patsalis, Polykarpos Christos; Al-Rashid, Fadi; Jánosi, Rolf Alexander; Nensa, Felix; Schlosser, Thomas Wilfried; Schlamann, Marc; Wendt, Daniel; Thielmann, Matthias; Kottenberg, Eva; Frey, Ulrich; et al.
Abstract: Background: Remote ischemic preconditioning (RIPC) reduces myocardial injury and improves clinical outcome in patients undergoing coronary revascularization, but only in the absence of propofol-anesthesia. We investigated whether RIPC provides protection of heart, kidneys and brain and improves outcome in patients undergoing transfemoral transcatheter aortic valve implantation (TF-TAVI). Methods: Patients undergoing TF-TAVI were randomized to receive RIPC (3 cycles of 5 min left upper arm ischemia and 5 min reperfusion) or placebo. The primary endpoint was myocardial injury, reflected by the area under the curve for serum troponin I concentrations (AUC-TnI) over the first 72 h. Secondary endpoints included the incidences of periprocedural myocardial infarction, delayed gadolinium enhancement on postprocedural cardiac MRI, acute kidney injury, periprocedural stroke, and the incidence and volume of new lesions on postprocedural cerebral MRI. All-cause and cardiovascular mortality and major adverse cardiac and cerebrovascular events (MACCE) were assessed over 1-year follow-up. A prespecified interim-analysis was performed after the last patient had completed 1-year follow-up (NCT02080299 ). Results: 100 consecutive patients were enrolled between September 2013 and June 2015. There were no significant between-group differences in the primary endpoint of peri-interventional myocardial injury (ratio RIPC/placebo AUC-TnI: 0.87, 95% CI: 0.57–1.34, p = 0.53) or the secondary endpoints of cardiac, renal and cerebral impairment. There was no significant treatment effect in subgroup-analyses of patients undergoing cardiac or cerebral MRI. Mortality and MACCE did not differ. No RIPC-related adverse events were observed. Conclusions: RIPC did neither protect heart, kidneys and brain nor improve clinical outcome in patients undergoing TF-TAVI.